An Evaluation of the Modules on Readings in Philippine History: Inputs for Enhancing the Modules - Michelle Gregorious; Edward Torrefranca; Susana Geno (Universidade Estadual de Alagoas, 2024)
Modular learning has been one of the resorted modalities due to restrictions brought about by the COVID-19 pandemic. Most educators, including Quezon City University academic personnel, were compelled to redesign course syllabi and develop instructional materials such as the writing of modules suited for distance learning. This study evaluated the module currently utilized in the Readings in Philippine History (RIPH) course and provided inputs for module enhancement. A descriptive method was employed to gather data from one hundred ninety-seven (197) students and nine (9) faculty members. The evaluation of faculty and students showed satisfaction with the module but the feedback revealed some lacking features and weaknesses in the modules, particularly in the content. Validation of various learning tools, like modules, should also be emphasized to ensure the quality of the educational material that is being provided. The inclusion of the student's academic performance measures the learning effectiveness, necessitating validated rubrics to assess students' outcomes through module utilization. Thus, the suggested improvements may provide future directions for the instructional materials as well as for teachers and students to achieve the main purpose even in a flexible learning environment.